Transitional justice and economic, social and cultural rights: contributions and challenges from a Latin American perspective - Méndez Royo, Daniela Paulina (2019)
Transitional justice has been historically linked to dealing with the legacy of massive and systematic civil and political rights violations. However, some scholars and practitioners have stressed the importance of including an economic, social and cultural rights perspective in transitional justice. This is a relatively new area of research, with limited analysis of the challenges or best ways to address economic, social and cultural rights through the transitional justice framework.